2017
DOI: 10.1016/j.amsu.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Three years evaluation of retained foreign bodies after surgery in Iran

Abstract: BackgroundMedical errors such as retained foreign bodies (RFB) during surgery are not well studied. To define risk factors associated with this type of error, we performed retrospective study.MethodsWe reviewed medical records for unintentional foreign object remaining in the body during surgery such as gender, age, surgery ward, and incident reports referred to several forensic medicine administrations as well as adverse effects of retained foreign bodies and methods for detection of them over a 3-years perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Yildirim et al investigated the diagnosis and management of retained surgical foreign bodies and recommended removal of the foreign body when identified in a symptomatic patient. However, for asymptomatic and selected cases, he supported follow-up of the patient as the treatment of choice, particularly if exploring and removing the foreign body will bring more harm to the patient [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yildirim et al investigated the diagnosis and management of retained surgical foreign bodies and recommended removal of the foreign body when identified in a symptomatic patient. However, for asymptomatic and selected cases, he supported follow-up of the patient as the treatment of choice, particularly if exploring and removing the foreign body will bring more harm to the patient [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes they remain altogether asymptomatic. The clinical manifestation ranges from no symptoms at all to pain, sepsis, abscess, nonhealing wounds, fistulas and intestinal obstruction [ 1 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence might be even higher during emergency surgeries [ 6 ]. A surgical sponge is the most commonly reported retained item following surgery, whereas reports of retained needles and instruments are extremely rare [ 3 ]. There are cases of retained appendices epiploicae after surgery resembling a ‘boiled egg’ [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although World Health organization(WHO) and the Association of periOperative Registered Nurses (AORN) recommended that counting of surgical items would be performed for every surgical procedure (3) (11), similarly to the study(4), the respondents affirmed that surgical item count was performed in certain procedures such the abdomen surgeries as the abdominal size can lead to surgical objects cases' retention (4). Therefore, the observation that was done in different types of surgical procedures as the study done in the Iran on "Three years evaluation of retained foreign bodies after surgery" showed that unknown items retained in everybody hollows were included peritoneal hollow, thoracic cavity, gastrointestinal zone, urogenital tract, facial region, abdominalpelvic area with the majority of abdominal and peritoneal cavities(55,26%) and chest cavities(18.42%) (12). Surgical count must be done before each procedure to establish the baseline as the responsibility of Circulating and scrub nurses/midwives(14).…”
Section: Discussionmentioning
confidence: 99%